DANAMIC: Data analyzer of minimum inhibitory concentrations – Protocol to analyze antimicrobial susceptibility data - Javier Garcia-Ruiz; Maxim G. Ryadnov (STAR Protocols, 2022)
Summary: This protocol describes an open-source software developed to analyze experimental data obtained using antimicrobial susceptibility assays. We first describe experimental procedures for testing the activity of antimicrobial agents in vitro based on reference standards (BS EN ISO 20776-1:2020). We then describe the software protocol to analyze and convert the data obtained using these procedures into minimum inhibitory concentrations. This approach enables automated data analysis for microdilution assays and can be adapted for high-throughput antimicrobial screening. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.